Comparison of robotic and coblation tongue base resection for obstructive sleep apnoea. (4th September 2017) - Hwang, C.S.; Kim, J.W.; Kim, J.W.; Lee, E.J.; Kim, C.‐H.; Yoon, J.‐H.; Cho, H.‐J.
Abstract : Objectives: To compare the efficacy and safety of transoral robotic surgery (TORS) with endoscope‐guided coblation tongue base resection. Design: Retrospective case‐control study. Setting: University‐based tertiary care medical center. Participants: Patients with obstructive sleep apnoea (OSA) who underwent endoscope‐guided tongue base coblation resection or transoral robotic surgery (TORS) in combination with lateral pharyngoplasty at a single institution in South Korea between April 2013 and December 2016 were investigated. Forty‐five patients who had moderate‐to‐severe OSA with tongue base collapse and a minimum follow‐up period of 6 months with postoperative polysomnography (PSG) were enrolled in this study. Main outcome measures: All patients underwent pre‐ and postoperative (at least 4 months after surgery) overnight PSG. Available information on results of the PSG, Epworth sleepiness scale and complications of the TORS and coblation groups were compared. Results: Postoperative PSG studies showed improved sleep quality for most patients. The mean postoperative apnoea‐hypopnea index (AHI) was reduced significantly from 45.0 to 17.0 events/h ( P < .0001) in the TORS group and from 45.6 to 16.2 events/h ( P < .0001) in the coblation group. The mean rates of improvement (AHI reduction > 50%) were 75.0% in TORS patients and 62.1% in coblation patients and the difference was not significant. Less frequent postoperative morbidity, including bleeding, taste dysfunction and foreign body sensation, was recorded in TORS patients. Conclusions: Both the coblation and TORS groups showed similar surgical outcomes, TORS achieved PSG results non‐inferior to and complication rates comparable to coblation.